Logical-semantic knowledge model for the knowledge base of a lecturer - Serhii Dotsenko; Olga Banit; Dmytro Nor; Olga Morozova (Радіоелектронні і комп'ютерні системи)
The subject of this study is the process of synthesizing a graphical logical-semantic knowledge representation model with an open architecture for the knowledge base of a university lecturer. The purpose of the proposed model is to develop a lecturer’s knowledge base using a graphical logical-semantic knowledge representation model. The objectives of this study include: analysis of existing approaches to the formation of information management systems for organizing the educational process in higher education institutions; definition of the research methodology; analysis of the integrated four-factor architecture of the knowledge model about the existence and activities of the socio-economic ecosystem; formation of a three-factor logical-semantic knowledge representation model based on the results of the analysis; presentation of the practical implementation of the three-factor logical-semantic knowledge representation model for the lecturer’s knowledge base; and summarizing the research results and outlining future directions in the field of knowledge modeling for knowledge bases with open architecture. The methods used include an approach that identifies general patterns and hypotheses underlying the construction of lecturers’ knowledge bases to organize the educational process in higher education institutions. The theoretical foundation proposes using a logical-semantic model of semiotics knowledge because all known logical and logical-semantic knowledge models are representative objects of semiotics. The following results were obtained. The current focus of implementing information technologies in educational activities is on organizing educational processes in a distance format. At the same time, an important aspect of lecturers’ work—providing information supports for their methodological activities—has been overlooked. This work involves preparing initial materials, processing them, and forming the corresponding final materials in the form of textbooks, educational aids, lecture notes, methodological guidelines, and presentations. This paper proposes an architecture for a three-factor graphical logical-semantic knowledge representation model, which defines an algorithm to form the corresponding knowledge base. According to the authors, this knowledge base can be best implemented in Microsoft Excel. The advantage of this knowledge base model is its open architecture, as users hold administrator rights over the knowledge base. The user makes decisions about including relevant knowledge elements in the knowledge base. The inclusion of the "Students" factor in the knowledge base and subsequent recording of their participation results in classes ensures the possibility of providing these results to department and faculty management for further analysis. Conclusions. The architecture of the graphical logical-semantic knowledge representation model and its corresponding knowledge base ensures the resolution of tasks related to the preparation of methodological support for courses. It can also complement existing LMS (Learning Management Systems) and LCMS (Learning Content Management Systems). The next step in using the formed knowledge bases for relevant educational components (courses) is to create department knowledge based on these knowledge bases. This ensures the formation and preservation of the department's intellectual potential and transferability.